Does Hearing Preservation Surgery for Acoustic Neuromas Affect Tinnitus? - Kanzaki, Jin (1999)
Questionnaires returned from 202 patients who had undergone acoustic neuroma resection were analyzed with special reference to the effect on tinnitus of surgery that attempted to preserve hearing versus surgery that did not. We also examined the relationship between postoperative hearing and tinnitus following surgery to preserve hearing (103 patients, HP group). The incidence of preoperative tinnitus in the HP group was 78.6%; postoperatively it increased to 89.3% (p = 0.0367). The remaining 99 patients (non-HP) underwent labyrinthectomy during tumor resection. In this group tinnitus occurred in 72.7% preoperatively and in 67.3% postoperatively (p = 0.4097). Our findings show that when tinnitus was absent preoperatively, 85% of the HP group developed it postoperatively compared to 31% of patients in the non-HP group. The outcome of surgery to preserve hearing had no bearing on the loudness or annoyance of postoperative tinnitus. Although postoperative tinnitus is tolerable to most patients, they must be informed prior to surgery about its possible occurrence or worsening, especially if the goal is to preserve hearing.